2007
DOI: 10.1002/itdj.20059
|View full text |Cite
|
Sign up to set email alerts
|

Trust and distrust in online banking: Their role in developing countries

Abstract: Similar to the adoption of automatic teller machines, banks around the world are looking at online banking services as the next technology to reduce costs while maintaining or enhancing services to the customer. In developing countries, the low cost of online banking may enable banks to reach new customers, much like the cell phone offered new possibilities in telephony. Banks must understand, however, that the mediating use of technology increases interpersonal distance between banks and their customers, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(64 citation statements)
references
References 29 publications
5
59
0
Order By: Relevance
“…In many cases, individuals with low financial literacy will ignore banking applications and the benefits they may bring. Examining issues such as trust, may increase the use of mobile technologies in developing countries [47]. Considering the disadvantaged background, change in political structures for these countries does not culminate in economic power or wealth [23].…”
Section: Developing Countriesmentioning
confidence: 99%
“…In many cases, individuals with low financial literacy will ignore banking applications and the benefits they may bring. Examining issues such as trust, may increase the use of mobile technologies in developing countries [47]. Considering the disadvantaged background, change in political structures for these countries does not culminate in economic power or wealth [23].…”
Section: Developing Countriesmentioning
confidence: 99%
“…It has been found that consumer's attitudes toward online banking are influenced by the prior experience of computer and new technology [21]. The adoption of electronic banking forces consumers to consider concerns about password integrity, privacy, data encryption, hacking, and the protection of personal information [22]. Electronic banking requires perhaps the most consumer involvement, as it requires the consumer to maintain and regularly interact with additional technology (a computer and an Internet connection) [23].…”
Section: Consumer Attitude Towards M-bankingmentioning
confidence: 99%
“…In developed countries, consumer's attitude may be influence by previous experience in related technology and it has help to increase the adoption rate due to previous experience but, this may be slightly different in the developing countries were technology is just taking its stand. According the authors in [42], many bank customers have to consider the issue of hacking, the integrity of the password been used, data encryption and personal protection of information when it comes to adoption of electronic banking. This and many more are the challenges faced by bank customers and this has either affected their decision positively or negatively.…”
Section: Consumer Behaviour Towards Mobile Bankingmentioning
confidence: 99%